2016
DOI: 10.31018/jans.v8i3.998
|View full text |Cite
|
Sign up to set email alerts
|

Effect of water regimes on seed quality parameters of rice (Oryza sativa L.) grown under aerobic and wetland conditions

Abstract: A field experiment was conducted to know the effect of water regimes on seed quality parameters of rice and the was conducted by using factorial randomized complete block design, with two genotypes (BI-33 and Jaya) and two planting methods (Aerobic and Wetland). The resultants seeds were taken to conduct laboratory experiments pertaining to seed quality attributes and the studies revealed that the BI-33 under aerobic condition had shown a significantly higher seed quality with respect to germination (99%), mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…This might be due to less number of leachetes , increased amount reactive oxygen species and more number of living cells and ion exchange is in dual acceptable condition between plant and soil in case of aerobically developed genotype [11,19]. Similar results were reported by [9,10,18].…”
Section: Electrical Conductivity (Dscm -1 G -1 )supporting
confidence: 77%
See 1 more Smart Citation
“…This might be due to less number of leachetes , increased amount reactive oxygen species and more number of living cells and ion exchange is in dual acceptable condition between plant and soil in case of aerobically developed genotype [11,19]. Similar results were reported by [9,10,18].…”
Section: Electrical Conductivity (Dscm -1 G -1 )supporting
confidence: 77%
“…Higher amylase activity indicated that mobilization of reserve food materials and make available for the root and shoot growth hence the cultivars showing higher amylase activity resulted in higher germination [10,21].…”
Section: α-Amylase Activity (Cm)mentioning
confidence: 99%